2018
DOI: 10.1001/jama.2017.19130
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Screening and Treatment With Breast Cancer Mortality by Molecular Subtype in US Women, 2000-2012

Abstract: In this simulation modeling study that projected trends in breast cancer mortality rates among US women, decreases in overall breast cancer mortality from 2000 to 2012 were associated with advances in screening and in adjuvant therapy, although the associations varied by breast cancer molecular subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
195
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(207 citation statements)
references
References 35 publications
0
195
1
3
Order By: Relevance
“…This is in contrast to previous studies, which documented that racial disparities in survival were greatest for HR‐positive/luminal breast cancers . Triple‐negative breast cancers have a poorer prognosis compared with other subtypes, in part because this subtype is more likely to be diagnosed at an advanced stage, and the development of targeted therapies has lagged behind . Notably, a recent US population‐based study found that 4‐year relative survival was ≥95% for patients diagnosed with stage I disease across all breast cancer subtypes …”
Section: Selected Findingscontrasting
confidence: 68%
“…This is in contrast to previous studies, which documented that racial disparities in survival were greatest for HR‐positive/luminal breast cancers . Triple‐negative breast cancers have a poorer prognosis compared with other subtypes, in part because this subtype is more likely to be diagnosed at an advanced stage, and the development of targeted therapies has lagged behind . Notably, a recent US population‐based study found that 4‐year relative survival was ≥95% for patients diagnosed with stage I disease across all breast cancer subtypes …”
Section: Selected Findingscontrasting
confidence: 68%
“…The continued decreases in death rates for female breast cancer, prostate cancer, and colorectal cancer largely reflect improved early detection and more effective treatments . Because mammography use has been stable since the early 2000s, the recent decrease in breast cancer death rates may largely reflect improvement in treatments, such as targeted therapies . The use of prostate‐specific antigen testing has substantially decreased following the US Preventive Services Task Force recommendations against routine testing for men aged 75 and older in 2008 and for all ages in 2012, which may have contributed to the less rapid decline in prostate cancer death rates during the most recent years compared with the previous period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relative contribution of screening versus treatment will depend on the screening uptake rate, the sensitivity of the protocol, and access to state‐of‐the‐art treatment. Likewise, exercises in modeling based on estimation of the short‐term effect of screening using aggregate data, without being able to distinguish between individual women who are or are not screened, also cannot measure the true impact of screening . To date, no advance in therapy has been able to overcome the prognostic disadvantage of being diagnosed with a lymph node‐positive tumor.…”
Section: Discussionmentioning
confidence: 99%